Preparation method of integrated platinum group metal gas diffusion catalyst layer

Through the preparation of the integrated platinum group metal gas diffusion catalyst layer, the problem of catalyst fixation and dispersion is solved, and the stability and activity of the catalyst are improved, which is suitable for the large-scale application of electrolytic hydrogen production technology.

CN119307971APending Publication Date: 2025-01-14HUAYI NEW ENERGY MATERIALS (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411100295.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, it is difficult to achieve efficient mass transfer between the catalytic layer and the gas diffusion layer in close fit. Traditional catalyst preparation requires a large amount of binder, resulting in catalyst toxicity and performance degradation, limiting large-scale applications.

Method used

Using the preparation method of an integrated platinum group metal gas diffusion catalytic layer, the zinc-based organometallic skeleton and polyacrylonitrile were mixed and spinned, and the carbon fiber layer with multi-stage pores was carbonized at high temperature, and impregnated in the platinum group metal salt solution to avoid The binder is used to achieve the fixation and dispersion of the catalyst.

Benefits of technology

The stability and activity of the catalyst are improved, aggregation and dissolution are avoided, the transmission of gas and water is promoted, and the efficient mass transfer of the three-phase interface is improved, which is suitable for applications in the fields of large-scale production and energy conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307971A_ABST
    Figure CN119307971A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an integrated platinum group metal gas diffusion catalyst layer, which comprises the following steps: (1) mixing a zinc-based organic metal framework, polyacrylonitrile and N, N-dimethylformamide to obtain an electrostatic spinning precursor solution; (2) spinning the electrostatic spinning precursor solution by using an electrostatic spinning machine, and collecting to obtain a Zn-MOF fiber layer; (3) the Zn-MOF fiber layer is placed in inert gas for high-temperature carbonization, the carbonization temperature is 700-1000 DEG C, and a Zn-containing N-doped carbon fiber layer is obtained; and (4) dipping the Zn-containing N-doped carbon fiber layer in a platinum group metal salt solution at 20-60 DEG C for 2-24 hours, taking out and drying to obtain the platinum group metal gas diffusion catalyst layer. According to the invention, a catalytic layer (CL) and a gas diffusion layer (GDL) are combined into a whole, and adjustment of a multi-stage pore channel is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen production by electrolysis of water, relates to a platinum group catalyst used in hydrogen production by electrolysis of water, and in particular to a method for preparing an integrated platinum group metal gas diffusion catalytic layer. Background Art

[0002] The hydrogen evolution reaction (HER) in the cathode reaction of water electrolysis is a promising hydrogen supply pathway due to its wide water source and zero pollutant emissions. According to current reports, domestic and foreign research and development teams have developed various system catalysts for catalyzing HER. Among them, Pt-based materials with excellent H adsorption characteristics are recognized as the most effective HER catalysts and are also relatively mature catalysts in current industrial applications. In the current proton exchange membrane electrolyzer (PEM) structure, the gas diffusion layer (GDL) is tightly fitted with the surface of the catalytic layer (CL) by covering, which is not conducive to efficient mass transfer at the interface; and the preparation of traditional CL requires a large amount of binder, which reduces the electronic conductivity of the Pt-based catalyst itself and has different degrees of poisoning effect on the Pt-based catalyst; in addition, the coated CL easily leads to the aggregation / dissolution of nano-Pt-based catalysts, resulting in a decrease in PEM performance, which seriously limits its large-scale application in HER. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for preparing an integrated platinum group metal gas diffusion catalyst layer to achieve the integration of a catalyst layer (CL) and a gas diffusion layer (GDL) and the regulation of multi-stage pores. The prepared integrated gas diffusion catalyst layer has good catalyst fixation and dispersion effects, prevents catalyst aggregation / dissolution and can avoid the poisoning effect caused by the use of a binder.

[0004] To overcome the shortcomings of the existing technology.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for preparing an integrated platinum group metal gas diffusion catalyst layer comprises the following steps:

[0007] (1) mixing a zinc-based organic metal framework (Zn-MOF), polyacrylonitrile and N,N-dimethylformamide, stirring until the polyacrylonitrile is completely dissolved, and ultrasonically dispersing until the zinc-based organic metal framework is evenly dispersed to obtain an electrospinning precursor solution;

[0008] (2) spinning the electrospinning precursor solution using an electrospinning machine to collect and obtain a Zn-MOF fiber layer;

[0009] (3) placing the Zn-MOF fiber layer in an inert gas for high-temperature carbonization at a carbonization temperature of 700-1000° C. to obtain a Zn-containing N-doped carbon fiber layer;

[0010] (4) The Zn-containing N-doped carbon fiber layer is immersed in a platinum group metal salt solution at 20-60° C. for 2-24 hours, and then taken out and dried to obtain the platinum group metal gas diffusion catalyst layer.

[0011] In the present invention, the inert gas is mixed with hydrogen, and the mass ratio of the hydrogen in the mixed gas is 5-15%. Mixing hydrogen into the inert gas is beneficial to ensure the reduction of Zn.

[0012] In the present invention, the spinning voltage is 8-16 kV. By controlling the spinning voltage, Zn-MOF fiber layers with different thicknesses can be obtained.

[0013] In the present invention, the zinc-based organic metal framework is synthesized by adding zinc salt and dimethylimidazole to methanol solvent. By adjusting the ratio of methanol to water solution (V 甲醇 :V 水 ) can construct zinc-based organic metal frameworks of different morphologies, that is, multi-level channels with different pore sizes can be formed in the zinc-based organic metal framework. The zinc salt is one or more of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate, and hydrated zinc salts thereof.

[0014] In the present invention, one or more of boric acid, thioacetamide and triphenylphosphine are added to the electrospinning precursor solution. In this way, the element types in the Zn-MOF fiber layer can be adjusted, and then a porous carbon-based fiber layer doped with different elements (BN doping, SN doping, PN doping) can be derived.

[0015] In the present invention, the platinum group metal salt solution contains one, two or more platinum group metal ions. In this way, the present invention can construct a bimetallic or multimetallic alloy site of platinum group metals in the catalyst layer.

[0016] In the present invention, the platinum group metal salt solution is an aqueous solution of dichloride, trichloride, tetrachloride, nitrate or hydrochloric acid tetrachloride hydrate of a platinum group metal.

[0017] By adopting the above technical scheme, the integrated platinum group metal gas diffusion catalyst layer prepared by the present invention realizes the combination of the catalyst layer (CL) and the gas diffusion layer (GDL) and the adjustment of the multi-level pores. The adjustable multi-level pores are used to fix and disperse nanoparticles, which can protect the catalytically active metals from aggregation / dissolution to a large extent; and the adjustable multi-level pore structure is also conducive to the effective transmission of gas and water, and realizes efficient mass transfer at the three-phase interface during the catalytic process. In the preparation process, heteroatoms such as nitrogen, boron, phosphorus, and sulfur can also be introduced to improve the interaction between the metal and the carrier, promote the electron transfer at the interface, and further improve the activity of the Pt-based supported catalyst. In the catalyst layer prepared by this method, the platinum group metal catalyst particles have uniform size distribution and good catalytic stability, which can realize large-scale production and have broad application prospects in the field of energy conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the preparation principle of the Zn-MOF fiber layer of Example 1;

[0019] Figure 2 This is a schematic diagram of the preparation principle of the Pt metal integrated gas diffusion catalyst layer of Example 15;

[0020] Figure 3 The physical image and SEM image of the Zn-MOF fiber layer of Example 1 and the Zn-MOF fiber layer after carbonization;

[0021] Figures 4a to 4c The following are scanning electron microscope photos of Zn-MOF fibers prepared in Examples 1 to 3. Figure 4a The spun fibers were obtained under 8 kV voltage. Figure 4b The spun fibers were obtained under 12 kV voltage. Figure 4c The spun fibers produced under 16 kV voltage condition are shown;

[0022] Figure 5 The nitrogen adsorption and desorption capacity curves of the Zn-MOF fiber layers prepared in Examples 3 to 6 respectively after being carbonized at different temperatures;

[0023] Figure 6a This is a scanning electron microscope photo of the Zn-MOF prepared in Example 3;

[0024] Figure 6b This is a scanning electron microscope photograph of the Zn-MOF prepared in Example 11;

[0025] Figure 7 This is a linear sweep voltammetry (LSV) test result curve diagram of ZFS-N-Pt, ZFS-BN-Pt, ZFS-SN-Pt, and ZFS-PN-Pt corresponding to Example 3, Example 12 to Example 14.

[0026] Figure 8 The platinum metal gas diffusion catalyst layer (ZFS-BN-Pt) prepared in Example 12 was assembled into a PEM at a constant current density (1 A / cm 2 ) under 500h stability electrochemical test result curve:

[0027] Figure 9a The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of Example 12 before the stability test are shown in FIG.

[0028] Figure 9b The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of Example 12 after stability testing are shown in FIG.

[0029] Fig.10 The PEM assembled with different platinum metal gas diffusion catalyst layers was operated at a constant current density (1A / cm 2 ) under 500h stability electrochemical test result curve. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with examples, but the present invention is not limited to these specific embodiments.

[0031] Example 1

[0032] like Figure 1 As shown, the preparation steps of this embodiment are:

[0033] (1) Disperse 0.14 mol Zn(NO3)2·6H2O and 0.21 mol 2-methylimidazole in 400 mL methanol solution (V 甲醇 :V 水 =10:0), stirred vigorously by magnetic force for 30 min, and then allowed to stand at room temperature. After 24 hours, centrifuged at 6000 rpm for 10 min, and the white precipitate was harvested, which was the zinc-based organic metal framework (Zn-MOF), which was thoroughly washed with methanol and then dried in a vacuum oven overnight;

[0034] (2) 1 g Zn-MOF, 1 g polyacrylonitrile (PAN) and 9 g N,N-dimethylformamide / DMF were mixed and stirred at 70 °C until the polyacrylonitrile was completely dissolved, and ultrasonically dispersed until the Zn-MOF was uniformly dispersed to obtain an electrospinning precursor solution;

[0035] (3) spinning the electrospinning precursor solution using an electrospinning machine at room temperature, 30% humidity, and 8 kV voltage to collect and obtain a Zn-MOF fiber layer;

[0036] (4) The Zn-MOF fiber layer was placed in a hydrogen-argon (H2 / Ar) mixed gas (the mass content of hydrogen in the mixed gas was 10%) and carbonized at 900°C for 4 hours to obtain a Zn-containing N-doped carbon fiber layer.

[0037] Example 2

[0038] Compared with Example 1, the spinning voltage in step (2) of this embodiment is adjusted to 12Kv, and the rest is the same as Example 1.

[0039] Example 3

[0040] Compared with Example 1, the spinning voltage in step (2) of this embodiment is adjusted to 16Kv, and the rest is the same as Example 1.

[0041] Figure 3 The actual image and SEM image of the Zn-MOF fiber layer of Example 1 and the Zn-MOF fiber layer after carbonization.

[0042] in, Figure 3 Figures a and b are actual photographs of the Zn-MOF fiber layer of Example 1, indicating the self-supporting layered structure of the Zn-MOF fiber layer on a macro scale and its bending flexibility. Figure c is a microscopic SEM image of the Zn-MOF fiber layer of Example 1, indicating the fiber structure on a micro scale. Figures d and e are actual photographs of the Zn-MOF fiber layer after carbonization of Example 1, indicating that the Zn-MOF fiber layer can still maintain a macroscopic self-supporting layered structure and its bending flexibility after carbonization. Figure f is a microscopic SEM image of the Zn-MOF fiber layer of Example 1 after carbonization. Compared with Figure c, it is found that the microscopic fiber structure of the Zn-MOF fiber layer before and after carbonization is well preserved.

[0043] In Examples 1 to 3, the electric field is regulated by adjusting the spinning voltage during the electrospinning process, thereby adjusting the thickness of the fibers in the Zn-MOF fiber layer. Figure 4a The spun fibers were produced under 8 kV voltage conditions and had a measured diameter of about 3.8 μm. Figure 4b The spun fibers were produced under 12 kV voltage, and the diameter was measured to be about 2 μm; Figure 4b The spun fibers were obtained under 16 kV voltage, and the diameter was measured to be about 0.6-0.75 μm. It can be seen that the higher the spinning voltage, the thinner the spun fibers.

[0044] Example 4

[0045] Compared with Example 3, the carbonization temperature in step (4) of this example is adjusted to 700° C., and the rest is the same as Example 3.

[0046] Example 5

[0047] Compared with Example 3, the carbonization temperature in step (4) of this example is adjusted to 800° C., and the rest is the same as Example 3.

[0048] Example 6

[0049] Compared with Example 3, the carbonization temperature in step (4) of this example is adjusted to 1000° C., and the rest is the same as Example 3.

[0050] The pore size characteristics of the Zn-containing N-doped carbon fiber layers prepared at different carbonization temperatures in Examples 3 to 6 were analyzed, and the test data are shown in Table 1.

[0051] Table 1

[0052]

[0053] As can be seen from Table 1, the internal pore size characteristics of the carbonized carbon fiber layer at different calcination temperatures are different. As the calcination temperature increases from 700°C to 1000°C, its specific surface area increases from low to high. However, when the temperature reaches 1000°C, the specific surface area decreases instead. This is mainly due to the fact that the carbonization temperature of Example 6 is too high when the calcination temperature reaches 1000°C, which causes the internal micropores to collapse and transform into mesopores; the calcination temperature of Example 4 is relatively too low, which is not conducive to the distribution of the multi-level gradient internal pore size structure. Example 3 shows a higher specific surface area (985.71m2 g -1 ), with a higher pore volume of 0.721 cm 3 g -1 (mesopore volume: micropore volume = 1:1). Therefore, the multi-level pore distribution of the Zn-MOF carbon fiber layer can be achieved by adjusting the calcination temperature.

[0054] In addition, from Figure 5 It can be seen that during the temperature change from 700 to 1000℃, when the relative pressure P / P0 is in the low pressure range of 0-0.1, the adsorption amount rises rapidly and then decreases, indicating that the microporous structure in the micropores first increases and then decreases; when the relative pressure P / P0 is in the medium pressure range of 0.1-0.9, there is an increasingly obvious adsorption hysteresis loop, and then decreases, indicating that the proportion of mesoporous structure first increases and then decreases; when the relative pressure P / P0 is in the high pressure range of 0.9-1.0, the adsorption amount rises rapidly, and the presence of macroporous structure becomes higher and higher. Figure 5 This fully demonstrates that the internal pore size characteristics of the carbon fiber layer carbonized at different calcination temperatures are different, so the multi-level pore distribution of the Zn-MOF carbon fiber layer can be achieved by adjusting the calcination temperature.

[0055] Example 7

[0056] Compared with Example 3, in step (1), the volume ratio of methanol to water is adjusted to V 甲醇 :V水 =8:2, and the rest are the same as in Example 3.

[0057] Example 8

[0058] Compared with Example 3, in step (1), the volume ratio of methanol to water is adjusted to V 甲醇 :V 水 =6:4, and the rest are the same as in Example 3.

[0059] Example 9

[0060] Compared with Example 3, in step (1), the volume ratio of methanol to water is adjusted to V 甲醇 :V 水 =4:6, and the rest are the same as in Example 3.

[0061] Example 10

[0062] Compared with Example 3, in step (1), the volume ratio of methanol to water is adjusted to V 甲醇 :V 水 =2:8, and the rest are the same as in Example 3.

[0063] Embodiment 11

[0064] Compared with Example 3, in step (1), the volume ratio of methanol to water is adjusted to V 甲醇 :V 水 =0:10, and the rest are the same as in Example 3.

[0065] Compared with Example 3, in the above-mentioned Examples 7 to 11, the morphology of Zn-MOF can be adjusted by adjusting the volume ratio of methanol and water during the synthesis of Zn-MOF. Figure 6a The morphology of the Zn-MOF prepared in Example 3 is shown, which is a polyhedral structure. Figure 6b The morphology of the Zn-MOF prepared in Example 11 is shown, which is a layered stacking structure. As the water content in the solvent increases, the Zn-MOF structure changes from a polyhedron to a layered stacking structure, thereby affecting the pore size characteristics of the Zn-containing N-doped carbon fiber layer, as shown in Table 2

[0066] Table 2

[0067]

[0068] It can be illustrated through the above-mentioned Examples 1 to 11 that, if it is necessary to adjust the distribution of the multi-level channels of the Zn-MOF spinning fiber from the outside to the inside, the interfacial charge transfer resistance can be reduced by adjusting the spinning voltage, the calcination carbonization temperature, and the volume ratio of methanol and water. The better the interfacial electron transfer and interfacial mass transfer effects are, the more it can promote the effective transport of water and gas, so as to achieve efficient mass transfer at the three-phase interface during the catalytic process.

[0069] Example 12

[0070] Compared with Example 3, in step (2), 1 g Zn-MOF, 1 g polyacrylonitrile (PAN), 0.5 g boric acid, and 9 g N,N-dimethylformamide / DMF were mixed, and the rest was the same as Example 3. A BN-doped carbon fiber layer (ZFS-BN) was obtained.

[0071] Embodiment 13

[0072] Compared with Example 3, in step (2), 1 g Zn-MOF, 1 g polyacrylonitrile (PAN), 0.5 g thioacetamide, and 9 g N,N-dimethylformamide / DMF were mixed, and the rest was the same as Example 3. A SN-doped carbon fiber layer (ZFS-SN) was obtained.

[0073] Embodiment 14

[0074] Compared with Example 3, in step (2), 1 g Zn-MOF, 1 g polyacrylonitrile (PAN), 0.5 g triphenylphosphine, and 9 g N,N-dimethylformamide / DMF were mixed, and the rest was the same as Example 3. A PN-doped carbon fiber layer (ZFS-PN) was obtained.

[0075] The BN-, SN-, and PN-doped carbon fiber layers prepared in Examples 12 to 14 were subjected to X-ray photoelectron spectroscopy (XPS) analysis to determine the content of non-metallic doping elements in the BN-, SN-, and PN-doped carbon fiber layers. The test data are shown in Table 3.

[0076] Table 3

[0077] sample C / % N / % B / % S / % P / % Example 12 (ZFS-BN) 89.2 6.2 4.6 0 0 Example 13 (ZFS-SN) 90.5 6.3 0 3.2 0 Example 14 (ZFS-PN) 90.3 6.1 0 0 3.6

[0078] It can be seen from Table 3 that the nitrogen element in the carbon fiber layer doped with BN, SN, and PN mainly comes from Zn-MOF and PAN, which is basically maintained at about 6%. The B, S, and P elements mainly come from boric acid, thioacetamide, and triphenylphosphine dopants, and different proportions of impurity doping can be achieved by adjusting the dosage.

[0079] Take 1g of the Zn-containing N, BN, SN, and PN-doped carbon fiber layers prepared in Examples 3, 12, and 14, respectively, and place them in 100mL of a 0.1M PtCl4 solution at 50°C for 12h, take them out and dry them at 30°C to obtain a platinum metal gas diffusion catalyst layer (preparation principle reference Figure 2 ), named respectively: ZFS-N-Pt, ZFS-BN-Pt, ZFS-SN-Pt, ZFS-PN-Pt.

[0080] Linear sweep voltammetry (LSV) test Figure 7 As shown in the figure, ZFS-N-Pt, ZFS-BN-Pt, ZFS-SN-Pt, and ZFS-PN-Pt have a current density of 10 mA cm -2 The corresponding overpotentials are shown in Table 4, which are 60.1, 51.8, 56.1, and 53.7 mV respectively; the corresponding charge transfer resistances are shown in Table 4, which are 1.75, 1.32, 1.68, and 1.45 Ω respectively. Among them, the lower the overpotential, the better the catalytic activity; the lower the charge transfer resistance, the better the interfacial electron transfer and interfacial mass transfer effects. In other words, by doping with non-metallic elements and introducing heteroatoms such as nitrogen, boron, sulfur, and phosphorus into the carbon fiber layer, the interaction between the platinum group noble metal and the carrier can be improved, the interfacial charge transfer resistance can be reduced, the interfacial electron transfer can be promoted, and the activity of the Pt-based supported catalyst can be further improved.

[0081] Table 4

[0082]

[0083] Figure 8 The ZFS-BN-Pt of Example 12 was assembled into a PEM and then heated to 1 A / cm 2 Under the current density, the corresponding test voltage basically did not change, indicating the continuous stability of ZFS-BN-Pt catalytic hydrogen production, and no obvious performance degradation occurred within 500 hours.

[0084] Figure 9a This is a SEM scanning electron microscope photograph of ZFS-BN-Pt of Example 12, showing the microscopic fiber structure of the ZFS-BN-Pt gas diffusion catalyst layer. The TEM transmission electron microscope photograph shows that the Pt nanoparticles (2-5 nm) on the surface of ZFS-BN-Pt have a good dispersion effect (no nanoparticle stacking and agglomeration occurs); Figure 9bThis is the SEM scanning electron microscope photograph of ZFS-BN-Pt of Example 12, which shows that after a long period (500 hours) of catalytic hydrogen production process, the microscopic fiber structure of the ZFS-BN-Pt gas diffusion catalyst layer remains stable and no fiber corrosion occurs. The TEM transmission electron microscope photograph shows that after the ZFS-BN-Pt stability test (500 hours), the Pt nanoparticles (2-5nm) on its surface still maintain good dispersion characteristics, and there is no shedding, corrosion, dissolution, and stacking agglomeration.

[0085] Embodiment 15

[0086] Take 1 g of the Zn-containing BN-doped carbon fiber layer obtained in Example 12 and place it in 100 mL of 0.1 M H2PtCl6 solution and immerse it at 50°C for 12 h. Take it out and dry it at 30°C to obtain a platinum metal gas diffusion catalyst layer (ZFS-BN-Pt-1).

[0087] Example 16

[0088] Take 1 g of the Zn-containing BN-doped carbon fiber layer obtained in Example 12 and place it in 100 mL of 0.1 M RuCl3 solution and immerse it at 50°C for 12 h. Take it out and dry it at 30°C to obtain a ruthenium metal gas diffusion catalyst layer (ZFS-BN-Ru).

[0089] Embodiment 17

[0090] Take 1 g of the Zn-containing BN-doped carbon fiber layer obtained in Example 12 and place it in 100 mL of 0.1 M IrCl3 solution at 50°C for 12 h. Take it out and dry it at 30°C to obtain an iridium metal gas diffusion catalyst layer (ZFS-BN-Ir).

[0091] Embodiment 18

[0092] Take 1 g of the Zn-containing BN-doped carbon fiber layer obtained in Example 12 and place it in 100 mL of 0.1 M RhCl3 solution at 50°C for 12 h. Take it out and dry it at 30°C to obtain a rhodium metal gas diffusion catalyst layer (ZFS-BN-Rh).

[0093] The platinum group metal contents of the platinum group metal gas diffusion catalyst layers prepared in Example 12 and Example 15 to Example 18 were measured using inductively coupled plasma mass spectrometry (IPC-MS) technology as shown in Table 4.

[0094] Table 5

[0095]

[0096]

[0097] It can be seen from Table 5 that the mass fraction of precious metals (Pt, Ru, Ir, Rh) in ZFS-BN is basically maintained at about 5% after replacement with PtCl4, H2PtCl6, RuCl3, IrCl3, and RhCl3 solutions.

[0098] Embodiment 19

[0099] Compared with Example 15, in step (2), 0.5 g Zn-MOF, 1 g polyacrylonitrile (PAN) and 9 g N,N-dimethylformamide / DMF were mixed, stirred at 70° C. until PAN was completely dissolved, and ultrasonically dispersed until Zn-MOF was uniformly dispersed to obtain an electrospinning precursor solution. The rest was the same as Example 12.

[0100] Embodiment 20

[0101] Compared with Example 15, in step (2), 0.8 g Zn-MOF, 1 g polyacrylonitrile (PAN) and 9 g N,N-dimethylformamide / DMF were mixed, stirred at 70° C. until PAN was completely dissolved, and ultrasonically dispersed until Zn-MOF was uniformly dispersed to obtain an electrospinning precursor solution. The rest was the same as Example 12.

[0102] Embodiment 21

[0103] Compared with Example 15, in step (2), 1.2 g Zn-MOF, 1 g polyacrylonitrile (PAN) and 9 g N,N-dimethylformamide / DMF were mixed, stirred at 70° C. until PAN was completely dissolved, and ultrasonically dispersed until Zn-MOF was uniformly dispersed to obtain an electrospinning precursor solution. The rest was the same as Example 12.

[0104] Embodiment 22

[0105] Compared with Example 15, in step (2), 1.5 g Zn-MOF, 1 g polyacrylonitrile (PAN) and 9 g N,N-dimethylformamide / DMF were mixed, stirred at 70° C. until PAN was completely dissolved, and ultrasonically dispersed until Zn-MOF was uniformly dispersed to obtain an electrospinning precursor solution. The rest was the same as Example 12.

[0106] The platinum metal gas diffusion catalyst layers prepared in Examples 19 to 22 and Example 15 were named ZFS-5, ZFS-8, ZFS-12, ZFS-15, and ZFS-10, respectively.

[0107] In Examples 19 to 22, compared with Example 15, the Zn-MOF content was adjusted during the preparation of the Zn-MOF fiber layer to control the regulation of the Zn element, and N-doped carbon fiber layers with different Zn mass percentages were prepared. The IPC-MS technology was used to measure the zinc content of the fiber layer and the Pt precious metal content after replacement, as shown in Table 6.

[0108] Table 6

[0109]

[0110] Therefore, the loading amount of Pt precious metal can be adjusted by adjusting the content of Zn-MOF. When the mass ratio of Zn-MOF:PAN>1:1, the retention rate of Zn metal element remains basically unchanged, mainly due to the excessive introduction of Zn-MOF and the volatilization of high temperature 900℃ zinc vapor. The constant current density (1A / cm 2 )500h stability electrochemical test Fig.10 As shown, the stability of ZFS-10, ZFS-12, and ZFS-15 is better than that of ZFS-5 and ZFS-8, indicating that the increase in Pt loading helps to improve the stability of constant current density; the initial potential of ZFS-10, ZFS-12, and ZFS-15 is lower than that of ZFS-5 and ZFS-8, indicating that the increase in Pt loading helps to reduce the potential of the catalytic process and can reduce energy consumption.

Claims

1. A method for preparing an integrated platinum group metal gas diffusion catalyst layer, characterized in that: The steps include: (1) mixing a zinc-based organic metal framework, polyacrylonitrile and N,N-dimethylformamide, stirring until the polyacrylonitrile is completely dissolved, and ultrasonically dispersing until the zinc-based organic metal framework is uniformly dispersed to obtain an electrospinning precursor solution; (2) spinning the electrospinning precursor solution using an electrospinning machine to collect and obtain a Zn-MOF fiber layer; (3) placing the Zn-MOF fiber layer in an inert gas for high-temperature carbonization at a carbonization temperature of 700-1000° C. to obtain a Zn-containing N-doped carbon fiber layer; (4) The Zn-containing N-doped carbon fiber layer is immersed in a platinum group metal salt solution at 20-60° C. for 2-24 hours, and then taken out and dried to obtain the platinum group metal gas diffusion catalyst layer.

2. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: The inert gas is mixed with hydrogen.

3. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 2, characterized in that: The mass proportion of the hydrogen in the mixed gas is 5-15%.

4. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: The spinning voltage is 8-16 kV.

5. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: The zinc-based organic metal framework is synthesized by adding zinc salt and 2-methylimidazole into methanol solvent.

6. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 5, characterized in that: The zinc salt is one or more of zinc chloride, zinc sulfate, zinc nitrate, and zinc acetate, or / and a hydrate of the zinc salt.

7. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: The mass ratio of the zinc-based organic metal framework to the polyacrylonitrile is (5-15):

10.

8. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: One or more of boric acid, thioacetamide and triphenylphosphine is added to the electrospinning precursor solution.

9. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: The platinum group metal salt solution contains one, two or more platinum group metal ions.

10. The method for preparing an integrated platinum group metal gas diffusion catalyst layer according to claim 1, characterized in that: The platinum group metal ions are derived from an aqueous solution of a salt or a hydrate of a platinum group element.